Muscle Tissue as a Surrogate for In Vitro Drug Release Testing of Parenteral Depot Microspheres - Kozak, Jan; Rabiskova, Miloslava; Lamprecht, Alf (AAPS PharmSciTech, 2021)
Despite the importance of drug release testing of parenteral depot formulations, the current in vitro methods still require ameliorations in biorelevance. We have investigated here the use of muscle tissue components to better mimic the intramuscular administration. For convenient handling, muscle tissue was used in form of a freeze-dried powder, and a reproducible process of incorporation of tested microspheres to an assembly of muscle tissue of standardized dimensions was successfully developed. Microspheres were prepared from various grades of poly(lactic-co-glycolic acid) (PLGA) or ethyl cellulose, entrapping flurbiprofen, lidocaine, or risperidone. The deposition of microspheres in the muscle tissue or addition of only isolated lipids into the medium accelerated the release rate of all model drugs from microspheres prepared from ester-terminated PLGA grades and ethyl cellulose, however, not from the acid-terminated PLGA grades. The addition of lipids into the release medium increased the solubility of all model drugs; nonetheless, also interactions of the lipids with the polymer matrix (ad- and absorption) might be responsible for the faster drug release. As the in vivo drug release from implants is also often faster than in simple buffers in vitro, these findings suggest that interactions with the tissue lipids may play an important role in these still unexplained observations.
Keywords: flurbiprofen; Flurbiprofen; Animals; svaly; lidokain; kopolymer kyseliny glykolové a mléčné; intramuscular; parenterální infuze; In Vitro Techniques; Drug Carriers; techniky in vitro; biorelevant; pomocné látky; prasata; depot microspheres; Drug Liberation; Lidocaine; risperidon; příprava léků; Risperidone; léky s prodlouženým účinkem; celulosa; Delayed-Action Preparations; Swine; Polylactic Acid-Polyglycolic Acid Copolymer; Infusions, Parenteral; nosiče léků; Muscles; Excipients; PLGA; Drug Compounding; zvířata; uvolňování léčiv; Microspheres; Cellulose; mikrosféry; in vitro release